Motor skill learning and its neurophysiology - Mang, C. S.; Borich, M. R.; Wadden, K. P.; Boyd, L. A.; Siengsukon, C. F. (Skill acquisition in sport: research, theory and practice, 2020)
In conclusion, repeatedly performing motor skills in practice stimulates experience-dependent plasticity throughout the brain. These changes are the result of alterations in the brain at cellular and systems levels of organization. Critically, neuroplasticity supports motor learning at all levels of expertise and performance gains are stimulated by experience and practice that is skill-specific and mediated by feedback/reward circuits. Our understanding of the neural basis of how elite athletes learn will continue to advance our understanding of the impact of highly repetitive motor training on an extremely adaptable nervous system. This work may help reveal how elite athletes consistentiy and successfully perform highiy skilled, complex movements during competition and continue to advance their skills through practice. As advanced techniques used to image the brain and quantify behavior are refined, the neural processes underlying sport-specific performance are increasingly available for inquiry and potentially for manipulation through intervention. These advances will offer novel breakthroughs for future training and evaluation strategies aimed at maximizing sport-specific skill learning.